2019
DOI: 10.3389/fnins.2019.01250
|View full text |Cite
|
Sign up to set email alerts
|

sEMG-Based Trunk Compensation Detection in Rehabilitation Training

Abstract: Stroke patients often use trunk to compensate for impaired upper limb motor function during upper limb rehabilitation training, which results in a reduced rehabilitation training effect. Detecting trunk compensations can improve the effect of rehabilitation training. This study investigates the feasibility of a surface electromyography-based trunk compensation detection (sEMG-bTCD) method. Five healthy subjects and nine stroke subjects with cognitive and comprehension skills were recruited to participate in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 50 publications
0
26
0
1
Order By: Relevance
“…After feature extraction, with a server configured with 48 GB graphics card and 128 GB of running memory, the mean processing delays of 1-2-3-4-5-6 ANFIS model were about 8, 10, 11, 15, 15, and 16 s, respectively. In addition, the study shows that sEMG signals can be used for compensation detection (Ma et al, 2019) and rehabilitation robot control (Koh et al, 2017). As the sEMG-ANFIS method was based on a 128 ms window, it can be combined with a compensation detection method to monitor the spasticity state and compensation pattern in real time and as feedback control in the application of a rehabilitation robot.…”
Section: Discussionmentioning
confidence: 99%
“…After feature extraction, with a server configured with 48 GB graphics card and 128 GB of running memory, the mean processing delays of 1-2-3-4-5-6 ANFIS model were about 8, 10, 11, 15, 15, and 16 s, respectively. In addition, the study shows that sEMG signals can be used for compensation detection (Ma et al, 2019) and rehabilitation robot control (Koh et al, 2017). As the sEMG-ANFIS method was based on a 128 ms window, it can be combined with a compensation detection method to monitor the spasticity state and compensation pattern in real time and as feedback control in the application of a rehabilitation robot.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological signal sensing technologies include electromyogram (8/72, 11% studies), electroencephalogram (EEG) [ 33 , 80 ], and fMRI [ 71 ] systems. According to the reviewed studies, sEMG signals of upper limb muscles (including, but not limited to, biceps, triceps, upper trapezius, pectoralis major, brachioradialis, anterior, middle, and posterior deltoids) and trunk muscles (left or right rectus abdominis, left or right obliquus externus abdominis, left or right thoracic erector spinae, left or right lumbar erector spinae, and descending part of the trapezius) not only helped to discriminate true recovery and compensation [ 29 , 30 , 33 , 84 ] but also could be used as features for automatic compensation detection [ 39 , 53 , 77 ]. Chen et al [ 77 ] confirmed that using a generative adversarial network with sEMG signals as features could achieve excellent detection performance (accuracy=94.58%, +1.15% to –1.15%) of trunk compensatory movements.…”
Section: Resultsmentioning
confidence: 99%
“…Stroke is considered to be one of the main causes of disability in the world Burton et al (2018) and about 80 % of stroke patients have upper limb motor dysfunction Ma et al (2019). That is why it is so important to find ways to assist in the rehabilitation process of these patients.…”
Section: Introductionmentioning
confidence: 99%